Glycocalyx Remodeling with Proteoglycan Mimetics Promotes Neural Specification in Embryonic Stem Cells - Huang, Mia L. (American Chemical Society, 2014)
[Image: see text] Growth factor (GF) signaling is a key determinant of stem cell fate. Interactions of GFs with their receptors are often mediated by heparan sulfate proteoglycans (HSPGs). Here, we report a cell surface engineering strategy that exploits the function of HSPGs to promote differentiation in embryonic stem cells (ESCs). We have generated synthetic neoproteoglycans (neoPGs) with affinity for the fibroblast growth factor 2 (FGF2) and introduced them into plasma membranes of ESCs deficient in HS biosynthesis. There, the neoPGs assumed the function of native HSPGs, rescued FGF2-mediated kinase activity, and promoted neural specification. This glycocalyx remodeling strategy is versatile and may be applicable to other types of differentiation.